Metabolic Reprograming of Microglia in the Regulation of the Innate Inflammatory Response - Lauro, Clotilde; Limatola, Cristina (Frontiers in Immunology, 2020)
Abstract Microglia sustain normal brain functions continuously monitoring cerebral parenchyma to detect neuronal activities and alteration of homeostatic processes. The metabolic pathways involved in microglia activity adapt at and contribute to cell phenotypes. While the mitochondrial oxidative phosphorylation is highly efficient in ATP production, glycolysis enables microglia with a faster rate of ATP production, with the generation of intermediates for cell growth and cytokine production. In macrophages, pro‐inflammatory stimuli induce a metabolic switch from oxidative phosphorylation to glycolysis, a phenomenon similar to the Warburg effect well characterized in tumor cells. Modification of metabolic functions allows macrophages to properly respond to a changing environment and many evidence suggest that, similarly to macrophages, microglial cells are capable of a plastic use of energy substrates. Neuroinflammation is a common condition in many neurodegenerative diseases and the metabolic reprograming of microglia has been reported in neurodegeneration. Here we review the existing data on microglia metabolism and the connections with neuroinflammatory diseases, highlighting how metabolic changes contribute to module the homeostatic functions of microglia.